2016
DOI: 10.1002/adem.201600475
|View full text |Cite
|
Sign up to set email alerts
|

On The Superior High Temperature Hardness of Precipitation Strengthened High Entropy Ni‐Based Alloys

Abstract: The microstructure and high temperature hardness of two face-centered cubic high entropy Ni-based alloys with L1 2 g 0 precipitates have been studied. Both alloys exhibit higher mixing entropy and with the advantages in lower density and lower cost of raw materials than conventional Ni-based superalloys. Their g 0 solvus are above 1 150 C, and the g-g 0 microstructure can be thermodynamically stable after isothermal ageing from 700 to 1 100 C for at least 500 h. By XRD peak deconvolution, positive lattice misf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…A further addition of Al or Ti into these LTMs-based HEAs can produce phase transformations [ 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ], and then lead to microstructural diversities due to the strong interactions between Al/Ti and LTMs, resulting in an enhancement of strength. It is primarily attributed to the coherent precipitation of intermetallic phases, such as L1 2 -Ni 3 Al from the FCC matrix [ 125 , 126 ], and B2-NiAl [ 110 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ] and L2 1 -Ni 2 AlTi [ 107 , 108 , 109 ] from the BCC matrix. As example, the (NiCoFeCr) 94 Ti 2 Al 4 (at.%) HEA possesses a special coherent microstructure with fine spherical L1 2 -(Ni 3 (Al,Ti)) nanoprecipitates in the FCC matrix, resulting in a significant strength improvement with a yield strength over 1 GPa [ 125 ].…”
Section: Precipitate Morphology and Precipitation Strengthening Inmentioning
confidence: 99%
See 1 more Smart Citation
“…A further addition of Al or Ti into these LTMs-based HEAs can produce phase transformations [ 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ], and then lead to microstructural diversities due to the strong interactions between Al/Ti and LTMs, resulting in an enhancement of strength. It is primarily attributed to the coherent precipitation of intermetallic phases, such as L1 2 -Ni 3 Al from the FCC matrix [ 125 , 126 ], and B2-NiAl [ 110 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ] and L2 1 -Ni 2 AlTi [ 107 , 108 , 109 ] from the BCC matrix. As example, the (NiCoFeCr) 94 Ti 2 Al 4 (at.%) HEA possesses a special coherent microstructure with fine spherical L1 2 -(Ni 3 (Al,Ti)) nanoprecipitates in the FCC matrix, resulting in a significant strength improvement with a yield strength over 1 GPa [ 125 ].…”
Section: Precipitate Morphology and Precipitation Strengthening Inmentioning
confidence: 99%
“…As example, the (NiCoFeCr) 94 Ti 2 Al 4 (at.%) HEA possesses a special coherent microstructure with fine spherical L1 2 -(Ni 3 (Al,Ti)) nanoprecipitates in the FCC matrix, resulting in a significant strength improvement with a yield strength over 1 GPa [ 125 ]. A newly-developed kind of high entropy Ni-based alloys, such as Ni 48.6 Al 10.3 Co 17 Cr 7.5 Fe 9.0 Ti 5.8 Ta 0.6 Mo 0.8 W 0.4 (at.%), exhibit a higher high-temperature hardness resulted from the γ′-L1 2 precipitation-strengthening of γ-FCC matrix, where the coherent γ/γ′ microstructure can be thermodynamically stable after aging from 700 °C to 1100 °C for at least 500 h [ 126 ]. It is noted that a small amount of Al addition in HEAs (e.g., Al 0.3 FeCoNiCr [ 115 , 116 , 117 ] and Al 8 Co 17 Cr 17 Cu 8 Fe 17 Ni 33 [ 127 ]) generally renders spherical L1 2 -Ni 3 Al particles precipitated in the FCC matrix, resulting in high strength and good ductility, similar to that in Ni-based superalloys [ 5 , 132 ].…”
Section: Precipitate Morphology and Precipitation Strengthening Inmentioning
confidence: 99%
“…Furthermore, since the addition of refractory elements can easily promote the formation of detrimental topological-close packed (TCP) phases, the fraction of TCP was designed to be less than 1 vol% while adjusting the refractory additions. The ingot of HESA was prepared by vacuum-arc-melting process followed by directional-solidification (DS) to produce columnar microstructure; the setup of DS casting furnace has been described in our previous work 15 . The solution-heat-treatment (SHT) was then conducted at 1210 °C for 10 h to homogenize chemical segregations, and followed by a primary aging at 1000 °C for 3 h and a secondary aging at 800 °C for 20 h to grow and refine the morphology of γ′ precipitates.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the composition of HESA in current study is Ni 47.9 Al 10.2 Co 16.9 Cr 7.4 Fe 8.9 Ti 5.8 Mo 0.9 Nb 1.2 W 0.4 C 0.4 (at%), so the calculated ΔS mix is 1.60 R, which is higher than those of conventional superalloys such as CM247LC (ΔS mix = 1.29 R), Rene′ N5 (ΔS mix = 1.22 R), and CMSX-2 (ΔS mix = 1.14 R). Previous studies have shown that the γ - γ′ microstructure of HESAs can remain stable against topologically-close-packed (TCP) phase formation from 700 to 1100 °C for at least 500 h 15 , and with enhanced γ′ solvus temperatures above 1150 °C 16 . Furthermore, HESAs have shown good resistances against high temperature oxidation and corrosion by forming protective Al 2 O 3 and Cr 2 O 3 , respectively 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In the Ni-based superalloys a face-centered cubic (fcc) matrix is strengthened by fine precipitates of a Ni 3 (Al, Ti) phase with an L1 2 structure [21]. Similar kind of microstructure (the fcc matrix with the L1 2 precipitates) can be produced in some HEAs [22][23][24][25][26][27][28]; in Refs. [25,27] such alloys have been referred to as high entropy superalloys (HESAs).…”
Section: Introductionmentioning
confidence: 97%